En camino de una comunidad científica: La Revista de Relaciones Internacionales. (1980-2015) - Cascante Segura, Carlos Humberto (2015)
From Latour theoritical concepts on scientifcommunities, this article analizes 35 yearsold “Revista de Relaciones Internacionales”(Review of Internantional Relations) experience,as a critical component in InternationalRelations discipline strengthening in theCosta Rica academic society. Also, it reflectson the biggest challenges that this publicationougth to face on years to come.